Altered Brain Functional Connectome in Migraine with and without Restless Legs Syndrome: A Resting-State Functional MRI Study - Yang, Fu-Chi; Chou, Kun-Hsien; Hsu, Ai-Ling; Fuh, Jong-Ling; Lirng, Jiing-Feng; Kao, Hung-Wen; Lin, Ching-Po; Wang, Shuu-Jiun (Frontiers in Neurology, 2018)
Background: Migraine is frequently comorbid with restless legs syndrome (RLS), both displaying functional connectivity (FC) alterations in multiple brain networks, although the neurological basis of this association is unknown. Methods: We performed resting-state functional magnetic resonance imaging and network-wise analysis of FC in migraine patients with and without RLS, and healthy controls. Network-based statistics (NBS) and composite FC matrix analyses were performed to identify the patterns of FC changes. Correlation analyses were performed to identify associations between alterations in FC and clinical profiles. Results: NBS results revealed both migraine patients with and without RLS exhibited lower FC than healthy controls in the dorsal attention, salience, default mode, cingulo-opercular, visual, fronto-parietal, auditory, and sensory/somatomotor networks. Further composite FC matrix analyses revealed differences in FC of the salience, default mode to subcortical and fronto-parietal, auditory to salience, and memory retrieval networks between migraine patients with and without RLS. There was a trend toward a negative association between RLS severity and cross-network abnormalities in the default mode to subcortical network. Discussion: Migraine patients with and without RLS exhibit disruptions of brain FC. Such findings suggest that these disorders are associated with differential neuropathological mechanisms and may aid in the future development of neuroimaging-driven biomarkers for these conditions.